POSITIVE VERSUS NEGATIVE COMMUNICATION STRATEGIES IN TASK-BASED LEARNING - Siti Rohani (TEFLIN Journal: A publication on the teaching and learning of English, 2013)
This study aimed at describing how the implementation of Task Based Learning (TBL) would shape or change studentsâ use of oral communication strategies. Studentsâ problems and strategies to solve the problems during the implementation of TBL were also explored. The study was a mixed method, employing both quantitative and qualitative analysis throughmulti-methods of questionnaire, interviews, focus group discussion, learning journals, and classroom observation. Participants were 26 second year students of the State Polytechnic of Malang. Data collection was conducted for one semester. Findingsshow linguistic and non-linguistic problems encountered by students during one-semester implementation of TBL. Students also performedincreased use of positive strategies but reduced use of negative strategies after the implementation of TBL.Â